Bacterial-Degradation of Pesticides Residue in Vegetables During Fermentation - Azizi, A.; Homayouni, A. (Asian Journal of Chemistry, 2010)
Investigation on potential of isolated lactic acid bacteria on the degradation of agricultural pesticides residue in fermentation process was carried out in present study. Selected pesticides were malathion and diazinon. The highest population of bacteria i.e. Lactobacilli, Streptococci, Leuconostoc and Pediococci, was observed in first 24 h of fermentation. After this period the cfu/mL decreased remarkably. The pH of the product reached to 4.0 after 24 h of fermentation and then decreased slowly, as after 72 h did not exceed 3.6. The mixture of lactic acid bacteria showed good capability of decreasing the malathion concentration from 3.5 to 0.5 mg kg-1 after 48 h of fermentation. Adapted microorganisms were able to grow in the culture media containing malathion and diazinon. Finally, isolated lactic acid bacteria were considerably more capable of decomposing the pesticides and reducing the pH when applied in mix culture.